Ultrahigh-strength hydrogel sponge with hierarchical porous structure as well as preparation method and application of ultrahigh-strength hydrogel sponge
Through high-temperature mixing and multi-step solvent exchange treatment, an ultra-high-strength hydrogel sponge with a graded porous structure was prepared, which solved the problem of mechanical modulus reduction caused by the improvement of porosity in the prior art, achieved the combination of high-strength, high porosity and elastic recovery performance, and expanded its potential in a variety of materials applications.
Patent Information
- Application Number
- CN202411673458.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
While increasing porosity to improve material transport efficiency, existing hydrogel sponges often weaken their inherent mechanical modulus, resulting in deformation and poor load-bearing capacity, limiting their potential in load-support bracket applications.
By mixing polyvinyl alcohol raw materials, hydrogen bond acceptors and paraffin at high temperature, sol-gel conversion is carried out, and ethanol, n-hexane and water are successively exchanged to prepare an ultra-high strength hydrogel sponge with a graded porous structure.
It has achieved the improvement of the strength and durability of hydrogel sponges on the basis of ensuring high porosity, and obtained materials that combine ultra-high strength, high porosity and elastic recovery performance, suitable for biomedical materials, flexible wearable devices and tissue engineering materials.
Smart Images

Figure CN119505343A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous hydrogel materials, and in particular to an ultra-high strength hydrogel sponge with a hierarchical porous structure and a preparation method and application thereof. Background Art
[0002] Hydrogel sponge is a porous material that can absorb a large amount of water, and has the hydrophilic softness of hydrogel and the lightness of sponge. In recent years, hydrogel sponges have been widely used in the fields of seawater evaporation, tissue engineering, biomedical materials, etc., and significant progress has been made in the preparation process, structure regulation and performance optimization of hydrogel sponges. For example, Chinese patent CN113817214A discloses a method for preparing a porous hydrogel sponge, in which a porogen is placed in a hydrogel solution formed by mixing sodium hyaluronate containing double bonds or gelatin containing double bonds and a photoinitiator, and a negative pressure vacuum is maintained until the hydrogel solution is cross-linked, and a porous hydrogel is obtained after removing the porogen, and freeze-dried to obtain a porous hydrogel sponge. The porous hydrogel sponge material prepared by this method has a controllable, uniform and interconnected pore structure, which effectively increases the porosity and specific surface area inside the hydrogel sponge. Chinese patent CN106916333A discloses a method for preparing a polyvinyl alcohol medical sponge, which comprises adding polyvinyl alcohol and starch into distilled water and stirring to dissolve, adding a cross-linking agent, an emulsifier and a foam stabilizer and stirring, adding an acid catalyst to carry out an acetalization cross-linking reaction, and heating and curing to obtain a polyvinyl alcohol medical sponge. The polyvinyl alcohol medical sponge prepared by the method has a through-open-pore structure and uniform pore size, and has good biocompatibility, good affinity, high porosity and fast liquid absorption rate. Chinese patent CN113599565A discloses a method for preparing a gradient-degradable medical sponge, comprising the following steps: constructing a rigid part: providing a first water-soluble cellulose derivative, and cross-linking it to form a hydrogel slurry with a first viscosity; constructing a flexible part: providing a second water-soluble cellulose derivative, and cross-linking it to form a hydrogel slurry with a second viscosity, wherein the second viscosity is less than the first viscosity; constructing a composite structure: mixing the hydrogel slurry with the first viscosity and the hydrogel slurry with the second viscosity to form a mixed slurry; vacuum freeze-drying the mixed slurry to form a sponge. The medical sponge prepared by this method has both a rigid structure and a flexible structure, and can achieve gradient degradation regulation and quantitative drug release.
[0003] The material transport efficiency of hydrogels, which relies on porous structures, is a key factor in determining their functional diversity. Increasing porosity can significantly improve material transfer efficiency, but the extreme increase in porosity of hydrogels synthesized by the above method usually weakens their inherent mechanical modulus, resulting in significant deformation and poor load-bearing capacity. The tensile fracture strength of hydrogel sponges is limited, and mechanical properties may produce adverse effects such as creep during long-term use or cyclic deformation, thereby shortening their service life. This defect severely limits the potential of porous hydrogels as load-bearing scaffolds in further applications. In view of the market's potential application demand for hydrogel sponge materials, how to improve their strength and durability while ensuring the high porosity of the sponge has become a challenge. Summary of the invention
[0004] In view of this, the object of the present invention is to provide an ultra-high strength hydrogel sponge with a hierarchical porous structure and a preparation method and application thereof. The hydrogel sponge provided by the present invention has high porosity and high strength.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing an ultra-high strength hydrogel sponge with a hierarchical porous structure, comprising the following steps:
[0007] Mixing polyvinyl alcohol raw materials, hydrogen bond acceptors and paraffin at high temperature to perform sol-gel transformation to obtain gel; the temperature of the high temperature mixing is ≥90°C; the temperature of the sol-gel transformation is ≤10°C;
[0008] The gel is sequentially subjected to ethanol exchange treatment, n-hexane exchange treatment and water exchange treatment to obtain an ultra-high strength hydrogel sponge with a hierarchical porous structure.
[0009] Preferably, the polyvinyl alcohol raw material includes polyvinyl alcohol and / or polyvinyl alcohol grafted polymer;
[0010] The weight average molecular weight of the polyvinyl alcohol raw material is 10 to 2000 kDa;
[0011] The alcoholysis degree of the polyvinyl alcohol is 75-99.9%.
[0012] Preferably, the hydrogen bond acceptor comprises dimethyl sulfoxide and / or N,N-dimethylformamide;
[0013] The mass ratio of the polyvinyl alcohol raw material to the hydrogen bond acceptor is 5-20:80-95.
[0014] Preferably, the mass ratio of the polyvinyl alcohol to the paraffin is 5-20:10-30.
[0015] Preferably, the high-temperature mixing comprises: dissolving the polyvinyl alcohol raw material in dimethyl sulfoxide, and then adding paraffin wax and stirring and mixing.
[0016] Preferably, the high temperature mixing temperature is 90-110°C;
[0017] The dissolution time is 1 to 6 hours.
[0018] Preferably, the temperature of the sol-gel transition is -5 to 10°C, and the time is 2 to 48 hours.
[0019] Preferably, the ethanol exchange treatment time is 24 to 72 hours;
[0020] The time of the n-hexane exchange treatment is 48 to 120 hours;
[0021] The water exchange treatment time is 24 to 72 hours;
[0022] The time interval for replacing the solvent during the ethanol exchange treatment, the n-hexane exchange treatment and the water exchange treatment is independently 4 to 8 hours.
[0023] The present invention also provides an ultra-high strength hydrogel sponge with a hierarchical porous structure obtained by the preparation method described in the above technical solution.
[0024] The present invention also provides the use of the ultra-high strength hydrogel sponge with a hierarchical porous structure described in the above technical solution in biomedical materials, flexible wearable devices or tissue engineering materials.
[0025] The present invention provides a method for preparing an ultra-high strength hydrogel sponge with a hierarchical porous structure, comprising the following steps: mixing polyvinyl alcohol raw materials, hydrogen bond receptors and paraffin at high temperature, performing sol-gel transformation, and obtaining a gel; the temperature of the high temperature mixing is ≥90°C; the temperature of the sol-gel transformation is ≤10°C; the gel is sequentially subjected to ethanol exchange treatment, n-hexane exchange treatment and water exchange treatment to obtain an ultra-high strength hydrogel sponge with a hierarchical porous structure. The present invention can inhibit the non-covalent interaction within / between polyvinyl alcohol (PVA) molecular chains and preferentially form hydrogen bonds with PVA by adding hydrogen bond receptors; during the high temperature mixing process, the PVA molecular chains have a stretched conformation and are evenly distributed; paraffin is used as a pore-forming agent to construct a macroporous structure in the gel network. The present invention is based on the strategy of crystal constraint template (i.e., cooling to induce sol-gel transition of the mixed solution obtained by high-temperature mixing) and one-pot integrated molding to prepare a gel with high mechanical strength; the coordinated multi-step solvent (ethanol, n-hexane and water) exchange strategy not only removes the paraffin pore-forming agent, but also shrinks the PVA molecular chains that were originally fully stretched and evenly arranged to form a large number of crystal domains and microporous structures, and on the basis of improving the pore structure and specific surface area inside the hydrogel sponge, ensures the ultra-high strength and elastic recovery performance of the hydrogel sponge, and obtains a hydrogel sponge material with ultra-high strength, high porosity and elastic recovery performance. Moreover, the preparation method provided by the present invention has simple preparation process steps, easy conditions, and is suitable for industrial production.
[0026] The hydrogel sponge provided by the present invention has a hierarchical porous structure. On the basis of ensuring the high porosity of the material, it also has excellent mechanical properties. It has broad application prospects in the fields of biomedical materials, flexible wearable devices and tissue engineering materials, and can be used to prepare soft material elastic stents and other devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a surface scanning electron micrograph of the ultra-high strength hydrogel sponge with a hierarchical porous structure in Example 1;
[0028] Figure 2 This is a cross-sectional scanning electron micrograph of the ultra-high strength hydrogel sponge with a hierarchical porous structure in Example 1;
[0029] Figure 3 This is a microscopic reconstruction image of the ultra-high strength hydrogel sponge with a hierarchical porous structure in Example 1 obtained by a high-resolution three-dimensional X-ray microscope;
[0030] Figure 4 The porosity statistics and pore distribution statistics of the ultra-high strength hydrogel sponge with a hierarchical porous structure in Example 1 of the present invention;
[0031] Figure 5The breaking tensile stress-strain curves of the ultra-high strength hydrogel sponges with hierarchical porous structures in Examples 1 to 3;
[0032] Figure 6 The compressive stress-strain curves of the original sample of ultra-high strength hydrogel sponge with hierarchical porous structure in Example 1 under different stretching times;
[0033] Figure 7 The compressive stress-strain curves of the recovered sample of the ultra-high strength hydrogel sponge with a hierarchical porous structure in Example 1 at different stretching times after being immersed in water for 2 hours;
[0034] Figure 8 This is a comparison diagram of the energy dissipation of the original sample and the recovered sample of the ultra-high strength hydrogel sponge with a hierarchical porous structure in Example 1 under different stretching times. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing an ultra-high strength hydrogel sponge with a hierarchical porous structure, comprising the following steps:
[0036] Mixing polyvinyl alcohol raw materials, hydrogen bond acceptors and paraffin at high temperature to perform sol-gel transformation to obtain gel; the temperature of the high temperature mixing is ≥90°C; the temperature of the sol-gel transformation is ≤10°C;
[0037] The gel is sequentially subjected to ethanol exchange treatment, n-hexane exchange treatment and water exchange treatment to obtain an ultra-high strength hydrogel sponge with a hierarchical porous structure.
[0038] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0039] The invention mixes polyvinyl alcohol raw materials, hydrogen bond receptors and paraffin at high temperature, performs sol-gel transformation and obtains gel; the temperature of the high temperature mixing is ≥90°C; the temperature of the sol-gel transformation is ≤10°C.
[0040] In the present invention, the polyvinyl alcohol raw material preferably includes polyvinyl alcohol and / or polyvinyl alcohol grafted polymer; the polyvinyl alcohol grafted polymer preferably includes citric acid grafted modified polyvinyl alcohol (CA-PVA) and / or polyethylene glycol grafted modified polyvinyl alcohol (PEG-PVA). In the present invention, the weight average molecular weight of the polyvinyl alcohol raw material is preferably 10 to 2000 kDa, and in specific embodiments, it can be 10 kDa, 50 kDa, 100 kDa, 146 kDa, 186 kDa, 200 kDa, 300 kDa, 400 kDa, 500 kDa, 1000 kDa, 1500 kDa or 2000 kDa; the alcoholysis degree of the polyvinyl alcohol is preferably 75 to 99.9%, and in specific embodiments, it can be 75%, 80%, 85%, 90%, 95%, 99% or 99.9%.
[0041] In the present invention, the hydrogen bond acceptor preferably includes dimethyl sulfoxide and / or N,N-dimethylformamide. The hydrogen bond acceptor can inhibit the non-covalent interaction within / between PVA molecular chains and preferentially form hydrogen bonds with PVA.
[0042] In the present invention, the mass ratio of the polyvinyl alcohol raw material to the hydrogen bond acceptor is preferably 5-20:80-95, and in specific embodiments it can be 5:80, 5:85, 5:90, 5:95, 10:80, 10:85, 10:90, 10:95, 15:80, 15:85, 15:90, 15:95, 20:80, 20:85, 20:90 or 20:95.
[0043] In the present invention, the mass ratio of the polyvinyl alcohol to the paraffin wax is preferably 5-20:10-30, and in specific embodiments can be 5:10, 5:15, 5:20, 5:25, 5:30, 10:10, 10:15, 10:25, 15:10, 15:20, 15:25, 20:10, 20:15 or 20:25. The present invention uses paraffin wax as a pore-forming agent to construct a macroporous structure in the gel network.
[0044] In the present invention, the high-temperature mixing preferably includes: dissolving the polyvinyl alcohol raw material in dimethyl sulfoxide, and then adding paraffin wax and stirring and mixing. In the present invention, the temperature of the high-temperature mixing is ≥90°C, preferably 90-110°C, and in specific embodiments it can be 90°C, 95°C, 100°C, 105°C or 110°C. In the present invention, the dissolution time is preferably 1-6h, and in specific embodiments it can be 1h, 2h, 3h, 4h, 5h or 6h; during the dissolution process, the PVA molecular chain has a stretched conformation and is evenly distributed. In the present invention, the stirring and mixing preferably includes a first stirring and mixing and a second stirring and mixing in sequence, the rotation speed of the first stirring and mixing is preferably 500-1000r / min, and in a specific embodiment it can be 500r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min; the time of the first stirring and mixing is preferably 1-4h, and in a specific embodiment it can be 1h, 2h, 3h or 4h; the rotation speed of the second stirring and mixing is preferably 6000-10000r / min, and in a specific embodiment it can be 6000r / min, 7000r / min, 8000r / min, 9000r / min or 10000r / min; the time of the second stirring and mixing is preferably 10-30min, and in a specific embodiment it can be 10min, 15min, 20min, 25min or 30min.
[0045] In the present invention, the temperature of the sol-gel transition is ≤10°C, preferably -5 to 10°C, and in specific embodiments, it can be -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C or 10°C; the time of the sol-gel transition is preferably 2 to 48h, and in specific embodiments, it can be 2h, 5h, 10h, 15h, 20h, 24h, 25h, 30h, 35h, 36h, 40h, 45h or 48h. The present invention is based on the strategy of crystal constraint template (i.e., the mixed solution obtained by high temperature mixing is induced to undergo sol-gel transition by cooling) and one-pot integrated molding to prepare a gel with high mechanical strength.
[0046] After obtaining the gel, the present invention sequentially performs ethanol exchange treatment, n-hexane exchange treatment and water exchange treatment on the gel to obtain an ultra-high strength hydrogel sponge with a hierarchical porous structure.
[0047] In the present invention, the temperature of the ethanol exchange treatment is preferably room temperature, and the time of the ethanol exchange treatment is preferably 24 to 72 hours, and in specific embodiments, it can be 24 hours, 25 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 35 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 45 hours, 48 hours, 49 hours, 50 hours, 52 hours, 54 hours, 55 hours, 56 hours, 60 hours, 63 hours, 64 hours, 65 hours, 66 hours, 68 hours, 70 hours or 72 hours. The present invention has no special restrictions on the amount of ethanol used, as long as the gel can be immersed. In the present invention, the time interval for changing the solvent (ethanol) during the ethanol exchange treatment is preferably 4 to 8 hours, and in specific embodiments, it can be 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.
[0048] In the present invention, the temperature of the n-hexane exchange treatment is preferably room temperature, and the time of the n-hexane exchange treatment is preferably 48 to 120 hours, and in specific embodiments it can be 24 hours, 25 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 35 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 45 hours, 48 hours, 49 hours, 50 hours, 52 hours, 54 hours, 55 hours, 56 hours, 60 hours , 63h, 64h, 65h, 66h, 68h, 70h, 72h, 75h, 76h, 77h, 78h, 80h, 84h, 85h, 88h, 90h, 91h, 92h, 95h, 96h, 98h, 100h, 102h, 104h, 105h, 108h, 110h, 112h, 114h, 115h, 116h, 119h or 120h. The present invention has no special limitation on the amount of n-hexane used, as long as it can immerse the gel. In the present invention, the time interval for replacing the solvent (n-hexane) during the n-hexane exchange treatment is preferably 4 to 8 hours, and in a specific embodiment it can be 4h, 5h, 6h, 7h or 8h.
[0049] In the present invention, the temperature of the water exchange treatment is preferably room temperature, the total time of the water exchange treatment is 24 to 72 hours, and in specific embodiments, it can be 24 hours, 25 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 35 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 45 hours, 48 hours, 49 hours, 50 hours, 52 hours, 54 hours, 55 hours, 56 hours, 60 hours, 63 hours, 64 hours, 65 hours, 66 hours, 68 hours, 70 hours or 72 hours; the number of water exchanges is preferably 2 to 4 times, and in specific embodiments, it can be 3 times; the water preferably includes deionized water. The present invention does not specifically limit the amount of water used, as long as it can immerse the gel. In the present invention, the time interval for replacing the solvent (water) during the water exchange treatment is preferably 4 to 8 hours, and in specific embodiments, it can be 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.
[0050] The present invention sequentially performs solvent exchange treatment in ethanol, n-hexane and water, during which not only the paraffin pore-forming agent is removed, but also the PVA molecular chains that were originally fully stretched and evenly arranged shrink and form a large number of crystal domains and microporous structures. On the basis of improving the pore structure and specific surface area inside the hydrogel, the ultra-high strength and elastic recovery performance of the hydrogel are guaranteed.
[0051] The present invention is based on the strategy of crystal constraint template (i.e., cooling to induce sol-gel transition of the mixed solution obtained by high-temperature mixing) and one-pot integrated molding to prepare a gel with high mechanical strength, and coordinates multi-step solvent exchange and pore structure to build a uniform and dense gel network, thereby achieving the overall structural toughening of the hydrogel sponge. The prepared hydrogel sponge has multi-level and interconnected pore structure characteristics and has excellent elastic recovery ability. Moreover, the preparation method provided by the present invention has simple preparation process steps, easy conditions, and is suitable for industrial production.
[0052] The present invention also provides an ultra-high strength hydrogel sponge with a hierarchical porous structure obtained by the preparation method described in the above technical solution. In the present invention, the porosity of the ultra-high strength hydrogel sponge with a hierarchical porous structure is preferably 60-90%, and in a specific embodiment, it can be 60%, 65%, 70%, 75%, 80%, 81.69%, 85% or 90%; the pore distribution of the ultra-high strength hydrogel sponge with a hierarchical porous structure is preferably 2-10μm, and in a specific embodiment, it can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm. The present invention induces a sol-gel transition in a mixed solution by cooling to prepare a gel with high mechanical strength; a multi-step solvent (ethanol, n-hexane and water) exchange strategy is coordinated to obtain a hydrogel sponge material with ultra-high strength, high porosity and elastic recovery performance.
[0053] The present invention also provides the use of the ultra-high strength hydrogel sponge with a hierarchical porous structure described in the above technical solution in biomedical materials, flexible wearable devices or tissue engineering materials. In the present invention, the biomedical material preferably includes a biomedical device material, and more preferably includes a soft elastic scaffold or an artificial joint cartilage material.
[0054] The ultra-high strength hydrogel sponge with a hierarchical porous structure provided by the present invention has ultra-high strength, high porosity and elastic recovery performance, as well as excellent mechanical properties. It has broad application prospects in the fields of biomedical materials, flexible wearable devices and tissue engineering materials, and can be used to prepare soft material elastic scaffolds and other devices.
[0055] To further illustrate the present invention, the ultra-high strength hydrogel sponge with a hierarchical porous structure provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0056] In the following examples, the weight average molecular weight of polyvinyl alcohol is 146-186 kDa, and the alcoholysis degree is 99%.
[0057] Example 1
[0058] Add 10g of polyvinyl alcohol to 90g of dimethyl sulfoxide, heat to 90°C in an oil bath and stir continuously for 4h, add 20g of paraffin, stir at 800r / min for 2h, stir at high speed at 8000r / min for 20min to obtain a mixed solution, pour it into a mold and put it in a refrigerator at 4°C for 6h, demold it, and obtain a gel. Immerse the gel in anhydrous ethanol at room temperature for 48h (replace ethanol every 6h), then immerse it in n-hexane for 96h (replace n-hexane every 6h), immerse it in deionized water for three water exchanges, and the total water exchange time is 48h (replace deionized water every 6h), and obtain an ultra-high strength hydrogel sponge with a hierarchical porous structure. Among them, the mass ratio of polyvinyl alcohol, dimethyl sulfoxide and paraffin is 10:90:20.
[0059] Example 2
[0060] An ultra-high strength hydrogel sponge with a hierarchical porous structure was prepared according to the method of Example 1, the only difference from Example 1 being that the mass ratio of polyvinyl alcohol, dimethyl sulfoxide and paraffin was 15:85:20.
[0061] Example 3
[0062] An ultra-high strength hydrogel sponge with a hierarchical porous structure was prepared according to the method of Example 1, the only difference from Example 1 being that the mass ratio of polyvinyl alcohol, dimethyl sulfoxide and paraffin was 20:80:20.
[0063] Test Case
[0064] 1. Characterization of hydrogel sponge structure
[0065] The surface SEM image of the ultra-high strength hydrogel sponge with hierarchical porous structure prepared in Example 1 is as follows: Figure 1 As shown, the cross-sectional SEM image is Figure 2 As shown in Figure 2, pore structures with different pore sizes can be observed on the surface and cross-section of the hydrogel sponge. The internal microscopic pore structure was reconstructed using a high-resolution three-dimensional X-ray microscope, as shown in Figure 2. Figure 3 As shown in the figure, it can be seen that the hydrogel sponge has interconnected pores. The porosity statistics and pore distribution statistics are shown in the figure. Figure 4As shown, according to the pore structure data statistics chart, the porosity of the hydrogel sponge is as high as 81.69%, and the pore distribution is 5.36±1.52μm.
[0066] 2. Mechanical properties test of hydrogel sponge
[0067] The mechanical properties of the ultra-high strength hydrogel sponges with hierarchical porous structures prepared in Examples 1 to 3 were tested using an electronic universal material testing machine (EZ-Test, SHIMADZU) (tensile mode, tensile rate of 50 mm / min). The hydrogel sponges to be tested were dumbbell-shaped samples with a gauge length of 13.5 mm and a width of 2 mm. The results are shown in Table 1. Figure 5 As shown, the results show that the tensile stress at break of the hydrogel sponges containing different mass fractions of polyvinyl alcohol is greater than 2 MPa.
[0068] The recovery ability of the ultra-high strength hydrogel sponge with a hierarchical porous structure in Example 1 (original sample) was tested. After the first stretching cycle test (strain: 150%), the hydrogel sponge was immersed in deionized water for 2 hours to recover, and then a subsequent cyclic stretching test was performed, with the number of cycles being 1 to 10.
[0069] Figure 6 is the compressive stress-strain curve of the original sample under different stretching times, Figure 7 The compressive stress-strain curves of the recovered samples at different stretching times after immersion in water for 2 hours. Figure 8 The energy dissipation comparison results of the original sample and the recovered sample at different stretching times are shown in the figure. Figure 6 to Figure 8 It can be seen that the initial stretching causes a certain degree of residual strain in the hydrogel sponge. After it recovers for 2 hours, the elastic modulus and the tensile stress at 150% strain do not decrease significantly in comparison, and no obvious difference is shown in the subsequent cyclic stretching test. This shows that the hydrogel sponge has excellent elastic recovery ability.
[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an ultra-high strength hydrogel sponge with a hierarchical porous structure, comprising the following steps: Mixing polyvinyl alcohol raw materials, hydrogen bond acceptors and paraffin at high temperature to perform sol-gel transformation to obtain gel; the temperature of the high temperature mixing is ≥90°C; the temperature of the sol-gel transformation is ≤10°C; The gel is sequentially subjected to ethanol exchange treatment, n-hexane exchange treatment and water exchange treatment to obtain an ultra-high strength hydrogel sponge with a hierarchical porous structure.
2. The preparation method according to claim 1, characterized in that: The polyvinyl alcohol raw material includes polyvinyl alcohol and / or polyvinyl alcohol graft polymer; The weight average molecular weight of the polyvinyl alcohol raw material is 10 to 2000 kDa; The alcoholysis degree of the polyvinyl alcohol is 75-99.9%.
3. The preparation method according to claim 1 or 2, characterized in that: The hydrogen bond acceptor includes dimethyl sulfoxide and / or N,N-dimethylformamide; The mass ratio of the polyvinyl alcohol raw material to the hydrogen bond acceptor is 5-20:80-95.
4. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the polyvinyl alcohol to the paraffin is 5-20:10-30.
5. The preparation method according to claim 1, characterized in that: The high-temperature mixing comprises: dissolving the polyvinyl alcohol raw material in dimethyl sulfoxide, and then adding paraffin and stirring and mixing.
6. The preparation method according to claim 5, characterized in that: The temperature of the high temperature mixing is 90-110°C; The dissolution time is 1 to 6 hours.
7. The preparation method according to claim 1, characterized in that: The temperature of the sol-gel transition is -5 to 10° C., and the time is 2 to 48 hours.
8. The preparation method according to claim 1, characterized in that: The ethanol exchange treatment time is 24 to 72 hours; The time of the n-hexane exchange treatment is 48 to 120 hours; The water exchange treatment time is 24 to 72 hours; The time interval for replacing the solvent during the ethanol exchange treatment, the n-hexane exchange treatment and the water exchange treatment is independently 4 to 8 hours.
9. The ultra-high strength hydrogel sponge with a hierarchical porous structure obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the ultra-high strength hydrogel sponge with a hierarchical porous structure according to claim 9 in biomedical materials, flexible wearable devices or tissue engineering materials.
Citation Information
Patent Citations
Medical polyvinyl alcohol sponge and preparation method
CN106916333A
Gradient degradation medical sponge and preparation method thereof
CN113599565A
Porous hydrogel sponge as well as preparation method and application thereof
CN113817214A
Method for preparing biocompatible high-strength three-dimensional connected porous PVA hydrogel
CN101544767A
Environment-friendly physically crosslinked self-lubricating hydrogel and preparation method thereof
CN112694621A